Use of SSA to detect structural changes in metallocenic ethylene/alfa-olefin copolymers and their free radical post-reactor modifications - Satti, Angel Jose (2016)
The successive self nucleation and annealing (SSA) methodology has been shown to be successful to characterize the lamellae structure of many polyolefins. The differences in molecular structure of metallocenic a-olefin copolymers with varied comonomer type and content were characterized by this technique with a conventional DSC. This thermo-structural characterization process was also applied to analyze the changes induced on a 1-octadecene - ethylene copolymer modified with different postreactor methods: several doses of gamma-radiation, peroxide modification and oxidative degradation.These modifications induced crosslinking and branching on the original copolymer affecting its molecular weight and the crystalline structure. The SSA technique revealed detailed changes in the lamellae formation of the materials obtained as a consequence of the different methods of modification employed in this work. Mainly, crosslinking and branching sites restrained the mobility and length of CH2 sequences to form lamellae, while degradation led to preferential chain scission at branched carbons making easier the formation of higher melting temperature lamellae.